Shaking off the neoliberal shackles: "democratic emergence" and the negotiation of democratic knowledge in the Middle East North Africa context. Issue 5 (4th July 2019) - Bridoux, Jeff
ABSTRACT: There is a general assumption in democracy promotion that liberal democracy is the panacea that will solve all political and economic problems faced by developing countries. Using the concept of "good society" as analytical prism, the analysis shows that while there is a rhetorical agreement as to what the "good society" entails, democracy promotion practices fail to allow for recipients' inclusion in the negotiation and delivery of the "good society". Contrasting US and Tunisian discourses on the "good society", the article argues that democracy promotion practices are underpinned by neoliberal parameters borne out from a reliance on the transition paradigm, which in turn leave little room to democracy promotion recipients to formulate knowledge claims supporting the emergence of alternative conceptions of the "good society". In contrast, the article opens up a reflective pathway to a negotiated democratic knowledge, which would reside in a paradigmatic change that consists in the abandonment of the transition paradigm in favour of a "democratic emergence" paradigm.